Analysing the determinants of Malaysian crude palm oil prices in short – run and long-run: an ARDL approach / Mohd Shahrin Bahar ... [et al.] - Bahar, Mohd Shahrin; Bujang, Imbarine; Karia, Abdul Aziz; Baharudin, Nurzahidah (Universiti Teknologi MARA Selangor, 2023)
This research investigates the determinants of Crude Palm Oil (CPO) prices, focusing on the influence of selected independent variables using an advanced Autoregressive Distributed Lag (ARDL) method. CPO, known for its affordability and versatility compared to other vegetable oils, plays a pivotal role in the global economy. Despite its significance, the complexity of its pricing dynamics, which are influenced by multifaceted factors, has not been sufficiently addressed in the literature. This study aims to bridge the gap by examining both short-run and long-run relationships between selected independent variables and CPO prices, which include CPO exports, production levels, export tax, stock levels, weather conditions, population growth, economic growth, global consumption, and prices of other vegetable oils like soybean and sunflower, as well as the exchange rate and Consumer Price Index (CPI). Utilising monthly frequency data from January 2004 to December 2021, the research integrates these variables into an ARDL model to assess their impact on CPO prices in Malaysia. The analysis reveals that both immediate and lagged values of these variables significantly influence CPO prices in the short run. In the long run, key determinants such as CPO exports and production, economic indicators like the CPI, and the prices of competitive vegetable oils emerge as influential factors. The diagnostic tests confirm the model’s stability through the robustness check. The research contributes valuable insights into the intricate dynamics governing CPO pricing, guiding informed decision-making for policy makers and CPO stakeholders.